Analisis Materi IPA dan Simulasi Pembelajaran IPA di Sekolah Dasar Kelas IV pada Tema “Pengaruh Gaya terhadap Benda” - Neneng Nurhayati; Oktarina Ramdhani; Yadi Heryadi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Science education in elementary schools plays a crucial role in shaping students’ early understanding of natural phenomena, including the concept of force and its effects on objects. However, many teachers still face challenges in delivering the material in a contextual and engaging way, which affects student participation in learning. This study aims to analyze the relevance of the science content on the theme “the effect of force on objects” and to evaluate the effectiveness of simulation-based learning in improving concept comprehension among fourth-grade students. A descriptive quantitative method was used with a simple experimental approach involving one class. The research instruments included observation, documentation, and posttest assessments. The results showed that 92.6% of students achieved the minimum mastery criteria after participating in the simulation-based learning process. These findings indicate that the use of simulations helps students better understand changes in motion and shape caused by force. The implication of this study highlights the importance of integrating interactive media and experiential learning approaches in science education at the elementary level to enhance student engagement and significantly improve learning outcomes.